The Snake-Stone - Doherty, Berlie (New York Oxford University Press, 2005)
Containing activities specifically tailored to support the KS3 Framework for Teaching English, this work helps students fulfill the Framework objectives. The activities include work on Speaking and Listening; and close text analysis, and the structure of playscripts. They act as a springboard for personal writing.
Include Illustrations
Keywords: Diving -- Adoption -- Birthmothers